2003
DOI: 10.2516/ogst:2003033
|View full text |Cite
|
Sign up to set email alerts
|

Limitations in Mtbe Biodegradation

Abstract: Résumé -Étapes limitantes dans la biodégradation du MTBE -La voie métabolique de dégra-dation du méthyl tertio butyl éther ou MTBE chez Mycobacterium austroafricanum IFP 2012 a été partiellement élucidée par identification des intermédiaires de dégradation. Elle nécessite l'induction de différentes activités enzymatiques. Au cours des premières étapes de la dégradation du MTBE en tertio butyl alcool (TBA), une même monooxygénase est responsable de l'oxydation du MTBE et du TBA avec une faible affinité pour le … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…MTBE biodegradation has also been demonstrated in laboratory studies under a variety of redox conditions, where the highest MTBE degradation rates were observed under aerobic conditions (45). It has thus been suggested that biodegradation of MTBE in the field is often limited by the environmental conditions (12,37) and, in particular, by the limited concentrations of oxygen typically found in fuel-contaminated aquifers. As a consequence of these findings, in situ bioremediation of MTBE has been successfully enhanced by addition of air, pure oxygen (biostimulation), or previously enriched MTBE-degrading microorganisms (bioaugmentation) (49).…”
mentioning
confidence: 93%
“…MTBE biodegradation has also been demonstrated in laboratory studies under a variety of redox conditions, where the highest MTBE degradation rates were observed under aerobic conditions (45). It has thus been suggested that biodegradation of MTBE in the field is often limited by the environmental conditions (12,37) and, in particular, by the limited concentrations of oxygen typically found in fuel-contaminated aquifers. As a consequence of these findings, in situ bioremediation of MTBE has been successfully enhanced by addition of air, pure oxygen (biostimulation), or previously enriched MTBE-degrading microorganisms (bioaugmentation) (49).…”
mentioning
confidence: 93%
“…Abiotic reactions or an esterase will then cleave TBF into TBA and formate (14). TBA is a key intermediate observed in various investigations (10,13,43,52 (17,52). Hydroxylation of a methyl group of TBA followed by two consecutive dehydrogenase steps yields 2-HIBA (Fig.…”
Section: Bacterialmentioning
confidence: 98%
“…1) (8,14,26,50,52). The reaction is believed to yield tert-butoxy methanol, an unstable and/or reactive intermediate (13,14,48,52) that may undergo dismutation to TBA and formaldehyde (19). Alternatively, a dehydrogenase reaction may form TBF (19,23,43).…”
Section: Bacterialmentioning
confidence: 99%
“…It is known that MTBE can be degraded by co-metabolism as was observed during growth of various microorganisms on different carbon substrates (Brusseau et al 1990;Bowman et al 1993;Fayolle et al 2003).…”
Section: Introductionmentioning
confidence: 99%